UJI DAYA HASIL DAN MUTU FISIOLOGIS BENIH BEBERAPA GENOTIPE SORGUM MANIS (Sorghum bicolor (L.) Moench) KOLEKSI BATAN - Muhammad Nurdiansyah Al Fikri; Elza Zuhry; Nurbaiti ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this research was to determine of yield potential and seed physiologic quality for some genotypes of BATAN’s sweet sorghum and also was to determinethe best genotypes of sweet sorghum beetwen the attempt genotypes. This research has conducted in Field Experiment and Plant Breeding laboratory Faculty of Agriculture University of Riau, Pekanbaru, from April 2013 until November 2013. The research has conducted experimentally using randomizedblock design (RBD) consist of 13 treatments and 3 replications that contained 39 experimental units. These treatments consist of 10 BATAN’s sweet sorghum strains, there are Patir 1, Patir 2, Patir 3,    Patir 4, Patir 5, Patir 6, Patir 7, Patir 8, Patir 9 and Patir 10; and 3 sweet sorghum varieties as a comparison, there are Kawali, Mandau and Pahat. The result suggested that Patir 10 strain has the highest of grain weight/m2 that is 378,85 g (3,78 ton/ha), and Patir 9 strain has the seed physiologic quality better than 3 sweet sorghum varieties as a comparison and ever sweet sorghum strains. Patir 10 and  Patir 9 strains has the highest yield and seed physiologic quality, even higher than 3 sweet soghum varieties, so that both sweet sorghum strains recommended to the next attempt. Keyword : Sorghum bicolor, seed, yield potential, physiologic quality